2011
DOI: 10.1080/00028487.2011.607040
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Feeding Success of Fast‐Growing Yellow Perch Larvae and Juveniles in Perturbed Boreal Lakes

Abstract: The principal objective of this study was to test the hypothesis that enhanced early growth of yellow perch Perca flavescens in lakes affected by forest harvesting was related to favorable feeding conditions after the perturbation. Yellow perch larvae and juveniles and their zooplankton prey were sampled three times in three unperturbed lakes and in three perturbed lakes where forest harvesting had occurred in the catchment 2 years earlier. Univariate and multivariate analyses of the diets of age‐0 yellow perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Fairchild ; Leclerc et al . ). The functional group of small‐sized filterers (group 3) contained genera Bosmina and Ceriodaphnia and plays a significant functional role in lakes as their occurrence is controlled by bottom‐up and top‐down processes (Zaret & Kerfoot ; Geller & Müller ; DeMott ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fairchild ; Leclerc et al . ). The functional group of small‐sized filterers (group 3) contained genera Bosmina and Ceriodaphnia and plays a significant functional role in lakes as their occurrence is controlled by bottom‐up and top‐down processes (Zaret & Kerfoot ; Geller & Müller ; DeMott ).…”
Section: Discussionmentioning
confidence: 97%
“…Sida, Limnosida and Latona are mostly restricted to vegetation (two former) or bottom substrata from where they filter food particles (Fl€ ossner 1972) but again provide implications on the food web structure due to their more or less specialized feeding habits and large size (e.g. Fairchild 1983;Leclerc et al 2011). The functional group of small-sized filterers (group 3) contained genera Bosmina and Ceriodaphnia and plays a significant functional role in lakes as their occurrence is controlled by bottom-up and top-down processes (Zaret & Kerfoot 1975;Geller & M€ uller 1981;DeMott 1982).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that cladocerans in general may exhibit higher predator avoidance capabilities relative to other zooplankton groups (Graeb et al, 2004;Pichlová-Ptáčníková and Vanderploeg, 2011). This is not the case for larger YP larvae and juveniles that do prey heavily on cladocerans in general, especially in the summer, when these prey reach their highest abundances (Makarewicz, 1993;Leclerc et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
“…Despite anecdotal evidence (Withers, 2013;E. McNaught, Central Michigan University and Rutherford, NOAA-GLERL personal communication); to our knowledge there are no previous peer-reviewed reports that dreissenid larvae are a significant prey item for YP or other fish larvae in the Great Lakes and were not in the diet of western Lake Erie YP larvae in the 1990s (Molloy et al, 1997;Bremigan et al, 2003;Leclerc et al, 2011). The invasive dreissenid zebra and quagga mussels arrived in the Great Lakes in the late 1980s and quickly became numerous throughout the lakes (Nicholls and Hopkins, 1993;Mills et al, 1994;Ricciardi, 2001;Karatayev et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…In fact, in other studies in the same area, it has been shown that lakes affected by forest harvesting had higher Daphnia spp. abundance than unperturbed lakes [15] , [39] . On the other hand, DOC concentrations have increased significantly in perturbed lakes in 2009.…”
Section: Discussionmentioning
confidence: 99%